A colonialidade em meu corpo : as mulheres que vivem em mim falam por si - Silva, Gabriella Santos da (2021)
Considering the need for academic productions made by black women, for black women, for the reconstitution of their stories in non-colonial formats, the present dissertation aimed to investigate how coloniality affected my body from childhood to adulthood, starting from the methodological proposal escrevivência (EVARISTO, 1980), I trace parallels with childhood, education, youth and violence against my female and black body to understand the emancipatory processes. The locus for the realization of the research is the historical and memory retake of my life in discussion with productions of authors who supported the proposal of this work. As theoretical contributions, I support myself in Conceição Evaristo to build the work from the perspective of escrevivência, I also base myself on the theoreticalmethodological reference of Aníbal Quijano, Achille Mbembe, Frantz Fanon, Santiago CastroGomez and Ramón Grosfoguel, of decolonial studies, conceiving a production that aims at a total break with coloniality, so that Latin American peoples have power over their own histories. For a better analysis and understanding, I also bring in intersectional black feminist researchers and black authors prior to intersectionality (Patricia Hill Collins, bell Hooks, Neusa Santos, Lélia Gonzales, Kimberlè Crenshaw), thus locating my writing from a black, female, Latin American, peripheral, and subjective body. From the analysis of my own narrative I identify some reflections of coloniality: a) It is necessary to understand oneself racially to walk against the juxtaposed violence in our bodies. b) Colonialism is violent and torturing and has caused me several social and psychological problems. c) We need to build our stories to get out of the white-heteronormative hegemonic centrality. d) Black women, I beg you: emancipate yourselves!